2019
DOI: 10.1101/540096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GNI-A1mediates trade-off between grain number and grain weight in tetraploid wheat

Abstract: 15Grain yield is a highly polygenic trait determined by the number of grains per unit area, as well as 16 by grain weight. In wheat, grain number and grain weight are usually negatively correlated. Yet, 17 the genetic basis underlying trade-off between the two is mostly unknown. Here, we fine-mapped 18 a grain weight QTL using wild emmer introgressions in a durum wheat background, and showed 19 that grain weight is associated with the GNI-A1 gene, a regulator of floret fertility. In-depth 20 characterization o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Currently, the best seed set rates in T. intermedium are as low as 30% and increasing seed set would be a Trends in Plant Science rapid way to boost yield. Information concerning the genetic basis for fertility and seed set has recently become available for wheat and barley [62,63]. The GNI1 gene encodes an HD-Zip I transcription factor and its mutations in wheat and barley have led to increased floret fertility, higher grain number per spike, and higher yields [63,64].…”
Section: Seed Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the best seed set rates in T. intermedium are as low as 30% and increasing seed set would be a Trends in Plant Science rapid way to boost yield. Information concerning the genetic basis for fertility and seed set has recently become available for wheat and barley [62,63]. The GNI1 gene encodes an HD-Zip I transcription factor and its mutations in wheat and barley have led to increased floret fertility, higher grain number per spike, and higher yields [63,64].…”
Section: Seed Setmentioning
confidence: 99%
“…Information concerning the genetic basis for fertility and seed set has recently become available for wheat and barley [62,63]. The GNI1 gene encodes an HD-Zip I transcription factor and its mutations in wheat and barley have led to increased floret fertility, higher grain number per spike, and higher yields [63,64]. Wheat GNI-A1 (SPT19245) has been under selection during domestication and its reduced function in domesticated wheat is the result of an Asn105Tyr mutation in the otherwise conserved HD domain.…”
Section: Seed Setmentioning
confidence: 99%
“…Final KW is the result of the interplay between potential kernel weight (sink) and the actual supply of assimilates per kernel during kernel filling (source). Therefore, GNI-A1 participates in the trade-off between kernel number and kernel weight due to alterations in the assimilate distribution [ 119 , 120 ]. In this sense, Marcotuli et al [ 121 ] identified three putative candidate genes for kernel number per spike.…”
Section: Genes Affecting Yield and Its Components In Durum Wheatmentioning
confidence: 99%
“…A recently cloned gene, GNI, on chromosome 2A shows pleiotropic effects on KPS and TKW [44]. However, owing to the location of its homoeologues on 2B, QTL-ple2B is not the same gene [44,45]. Given the high correlation between GFR and TKW, QTL-ple2B is a novel locus that explains the genetic basis of the trade-off between TKW (GFR) and SN.…”
Section: Genetic Basis Of Yield and Its Improvementmentioning
confidence: 99%